2013
DOI: 10.1007/s00595-013-0608-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of gelatin flakes, a new type of anti-adhesive material: a preliminary study of in vivo rat adhesion models

Abstract: To overcome the problems associated with sheet- or film-type anti-adhesive materials, we developed a new type of anti-adhesive material, gelatin flakes. We made two types of gelatin flakes with or without thermal cross-linking, and preliminarily examined their basic properties and the anti-adhesive efficacy using a rodent adhesion model. Both types of the gelatin flakes rapidly turned into gel and tightly attached the injured surfaces, absorbing the moisture and blood, when applied onto the abraded sites of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This study showed severe adhesions in the control group in which the fibrin glue sealing sheet was applied. In contrast, anti-adhesion effect of gelatin has been reported elsewhere [25,[27][28][29][30][31]. A thermally treated gelatin sheet, reinforced with bioabsorbable poly(glycolic acid) mesh, exhibited reduced formation of pleural and pericardial adhesion and inflammatory reaction in a canine model [29,30].…”
Section: Postoperative Adhesionsmentioning
confidence: 86%
See 1 more Smart Citation
“…This study showed severe adhesions in the control group in which the fibrin glue sealing sheet was applied. In contrast, anti-adhesion effect of gelatin has been reported elsewhere [25,[27][28][29][30][31]. A thermally treated gelatin sheet, reinforced with bioabsorbable poly(glycolic acid) mesh, exhibited reduced formation of pleural and pericardial adhesion and inflammatory reaction in a canine model [29,30].…”
Section: Postoperative Adhesionsmentioning
confidence: 86%
“…It has been reported that unstable glutaraldehyde polymer released from the glutaraldehyde crosslinked material caused cytotoxicity [26]. Alternatively, gelatin can be crosslinked by UV irradiation [27] or thermal treatment [28][29][30][31]. These techniques do not require chemical agents, and hence, are safer options.…”
Section: Surgical Hemostatic Agentsmentioning
confidence: 99%
“…Currently, medical absorbable anti-adhesion films [ 14 ] are most widely used both domestically and internationally, such as Seprafilm [ 15–17 ], Interceed [ 18 ] etc. Solid anti-adhesive film [ 19 ] has a physical barrier effect that can isolate inflammatory cells and inflammatory factors, and the effect is stable and long-lasting. However, it is challenging to cover irregular or large areas of injury, and the surgical exposure area is too large, so it is suitable for open surgery but not for minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The solution of this problem could be in the preparation of anti-adhesion materials based on biopolymers. 6,7 Among the numerous natural polymers, it is important to highlight pectin and chitosan as biodegradable, biocompatible, non-toxic, and bioadhesive polysaccharides, which can potentially be used to create new biomaterials. [8][9][10][11] Chitosan -a cationic polysaccharide, the deacetylated derivative of chitin, a natural polysaccharide -is the main component of the integument of arthropods and some fungi.…”
Section: Introductionmentioning
confidence: 99%